The Correlation between Vocabulary Mastery and Simple Essay Writing Skills in German - Amalia, Resky; Al Ilmullah, Syarifah Fatimah; Azizah, Laelah (Phonologie : Journal of Language and Literature, 2024)
Abstract. Abstract. The purpose of this research is to obtain data on the relationship between vocabulary mastery and simple essay writing skills in German for class IX students at SMA Negeri 14 Gowa. The population in this study were class IX Language students at SMA Negeri 14 Gowa, consisting of 1 class totaling 35 students. Data collection is through vocabulary mastery tests and simple essay writing skills tests. This research data was analyzed using the Product Moment correlation analysis technique. The results of this study show that there is a significant positive relationship between vocabulary mastery and the skill of writing simple essays in German, this is indicated by the value ????ℎ(0.759) > ???????? (0.344), with N = 35 at a significance level of 0.05%.Keyword: Vocabulary, write, mastery, skills